Peranan Analisis Jabatan Dalam Penempatan Pegawai (Studi Kasus Pada Bagian Organisasi Dan Tata Laksana Sekretariat Daerah Kota Binjai) - Raudah Azzahra Manurung; Muhammad Irwan Padli Nasution (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
Problems related to human resource management policies are very complex and difficult to solve, especially in the public organization sector. Job Analysis is a helpful tool for considering human resource policy development, management, institutions, and monitoring. The purpose of this study was to explain and analyze the role of job analysis in the placement of employees in the organization and management of the Binjai City Regional Secretariat. The research method used is descriptive research method with a qualitative approach. The result of this study is that workplace analytics is underutilized due to limited budget allocation, commitment from top managers, profit margins, and negative perceptions.